MOLECULAR CHARACTERIZATION AND ANTIBIOTIC RESISTANCE PROFILE OF ESCHERICHIA COLI ISOLATED FROM LIVER ABSCESS - Mohammad Nasar; Saqib Mumtaz; Muhammad Nadeem Hassan; Ijaz Ali; Sagar M Goyal; Nader Maher Sobhy; Sarra Grazza (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Bacterial liver abscess is the most common hepatic infection, which can lead to death. Escherichia coli is among the many species of bacteria that cause it. This study was conducted to isolate E. coli from liver abscess and then to characterise the bacteria’s molecular makeup and antibiotic resistance profile. Methods: A total of 208 stool samples were collected from patients showing symptoms of liver abscess. E. coli was isolated from these samples followed by identification by biochemical tests. Pure and biochemically positive colonies were confirmed by polymerase chain reaction. The disk diffusion method was used to ascertain the pattern of antibiotic resistance exhibited by E. coli isolates. Results: The PCR amplification efficiency was nearly 100% since all of the samples appeared at 284 molecular base pairs (bp), which is considered to be the optimal parameter assay. The antimicrobial susceptibility pattern showed that isolates were resistant to many drugs but 100% and 92% of the isolates were susceptible to imipenem and azithromycin, respectively. All isolates were resistant to ampicillin, vancomycin, and cefotaxime. This was followed by ceftazidime (72%), tetracycline (84%), trimethoprim (80%), streptomycin (96%), linezolid (92%), Teicoplanin (80%), nalidixic acid (84%), ciproﬂoxacin (92%), and chloramphenicol (72%). Conclusion: Multiple drug resistant E. coli is one of the causes of liver abscesses in humans.